CHARACTERIZATION OF TEMPORAL BIODEGRADATION OF RADIATA PINE BY GLOEOPHYLLUM TRABEUM THROUGH PRINCIPAL COMPONENT ANALYSIS-BASED TWO-DIMENSIONAL CORRELATION FTIR SPECTROSCOPY - Pozo, Claudio; Díaz-Visurraga, Judith; Contreras, David; Freer, Juanita; Rodríguez, Jaime (Journal of the Chilean Chemical Society, 2016)
Brown rot fungi produce a special pattern of wood decay. In the first stages of biodegradation, fast depolymerisation of holocellulose causes a rapid loss of wood strength while lignin is not substantially depolymerized. Fourier Transform Infrared Spectroscopy (FTIR) is a powerful tool for examining changes in wood chemistry. FTIR is an accurate, non-destructive technique, which usually requires a minimum of sample preparation and sample size. Principal component analysis-based two-dimensional (PCA2D) correlation spectroscopy of a spectral data set was applied to assess temporal brown-rot wood decay. Pinus radiata with soil support was degraded by brown rot fungi Gloeophyllum trabeum for a period of 0, 1, 2, 3, 4, 8, 12 and 16 weeks simulating the natural process of biodegradation. Decayed samples were monitored and analyzed periodically by FTIR. Most of the autopeaks had contributions from lignin, cellulose, and hemicelluloses. The main effect observed by PCA2D correlation was the significant decrease in the intensities of bands predominantly in the region of 2000-1000 cm-1, associated with polysaccharides in the biodegraded wood. An increase in the intensities of bands at 1698 and 1664 cm-1associated with the oxidation of wood components, mostly lignin, was also observed. Detailed analysis of asynchronous map showed that the wood oxidation began after the depolymerisation of polysaccharides. Figure 1. Reconstructed data of the FTIR spectra of the wood sample studied from loading vectors and scores of PC1, PC2 and PC3 in 1800–800 cm-1. Arrows indicate the directions of the changes in the intensity bands with increasing of biodegradation time. .